Upaya Meminimalkan Kecelakaan Kerja di PT. X dengan Pendekatan Behavior Based Safety (BBS) - Vincenzo Emmanuel Alim; Kriswanto Widiawan (Jurnal Titra, 2023)
PT. X is a company engaged in the plastic industry and focuses on providingplastic bags and geotextile products. The objective of the final project is to minimize workplace accidents using the behavior-based safety (BBS) approach at PT. X. The methods used in the behavior-based safety approach are called DO IT. The DO IT method consists of 4 steps: define, observe, intervene, and test. After conducting observations and analyzing the data, it was found that the circular loom, converting, and workshop processes have a good safety act score, above 80%. The extruder process has the lowest safe acts among the other processes, 71%. The extruder process has the lowest percentage of safe acts, so it is prioritized to be proposed for improvements to enhance operator behavior and reduce workplace accidents. After implementing the improvement, the percentage of safe acts in the extruder process increased to 87%.